2022
DOI: 10.21203/rs.3.rs-1318979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of sheep gastrointestinal nematodes on pasture in the tropical semiarid region of Brazil, using Bioverm® (Duddingtonia flagrans)

Abstract: We aimed to evaluate a Brazilian commercial formulation of the fungus Duddingtonia flagrans (Bioverm®) for controlling gastrointestinal nematodes in sheep kept on native pasture in the Caatinga biome, in the semiarid region of Brazil. Twenty ewes, aged between 12 and 18 months, were divided into two groups. In the treated group, each animal received 1 g of the Bioverm® product for each 10 kg of live weight, daily, together with commercial feed, for six months. In the control group, the animals received feed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The product Bioverm ® contains A. flagrans spores and is commercially available in Brazil. The product reduced the nematode egg counts per gram of faeces by around 75% in a recent 6-months study on controlling gastrointestinal nematodes in sheep (Rodrigues et al, 2022). Initial trials with potted crop plants and in greenhouses showed the potential of NTF against plant parasitic nematodes.…”
Section: Introductionmentioning
confidence: 98%
“…The product Bioverm ® contains A. flagrans spores and is commercially available in Brazil. The product reduced the nematode egg counts per gram of faeces by around 75% in a recent 6-months study on controlling gastrointestinal nematodes in sheep (Rodrigues et al, 2022). Initial trials with potted crop plants and in greenhouses showed the potential of NTF against plant parasitic nematodes.…”
Section: Introductionmentioning
confidence: 98%